Differential effects of natural Curcumin and chemically modified curcumin on inflammation and bone resorption in model of experimental periodontitis - Curylofo-Zotti, Fabiana Almeida; Elburki, Muna S.; Oliveira, Priscilla Aparecida [UNESP]; Cerri, Paulo Sérgio [UNESP]; Santos, Leandro Alves; Lee, Hsi-Ming; Johnson, Francis; Golub, Lorne M.; Rossa, Carlos; Guimarães-Stabili, Morgana Rodrigues (Elsevier, 2018)
Objective: The purpose of this study was to compare the effects of the oral administration of natural curcumin and a chemically modified curcumin (CMC2.24) on osteoclast-mediated bone resorption, apoptosis, and inflammation in a murine model of experimental periodontal disease. Design: Fifty male rats were distributed among the following treatment groups: (i) 2% carboxymethylcellulose, (ii) CMC2.24 30 mg/kg body weight, (iii) Curcumin 100 mg/kg body weight and (iv) no treatment. Compounds were administered daily by oral intubation over a 15-day period of time. Periodontal disease was induced by injections of LPS (lipopolysaccharide) into the gingival tissues three times per week. Contralateral sides were injected with the same volume of PBS (phosphate buffered saline) vehicle. After 15 days, hemimaxillae and gingival tissues were harvested. Bone resorption was assessed by μCT (microcomputer tomography). Formalin-fixed, paraffin embedded histological sections were stained with haematoxylin/eosin (H/E) for the assessment of cellular infiltrate or subjected to immunohistochemistry for detecting TRAP (tartrate-resistant acid phosphatase)-positive cells and caspase-3. Apoptosis was assessed in the gingival tissues by DNA fragmentation. Results: CMC2.24 and curcumin caused a significant reduction of the inflammatory cell infiltrate, however μCT analysis showed that only CMC2.24 reduced bone resorption and the number of TRAP-positive multinucleated cells (osteoclasts). Curcumin, but not CMC2.24, significantly reduced the number of apoptotic cells in the gingival tissues and of osteocytes in the alveolar bone crest. Conclusions: The results suggest that CMC2.24 and curcumin inhibit inflammation by different mechanisms, but only CMC2.24 was capable of reducing alveolar bone resorption in the LPS-induced model of periodontitis.
Keywords: Bone resorption; Chemically modified curcumin (CMC2.24); Inflammation; Lipopolysaccharide; Periodontal disease